Do You Know the Projects of Expeditionaries? (2010)
In the Expeditions to knowledge,the second stage of EAFIT Children's University, children and young people live an experience of formative research in an area of knowledge of their interest. They answer questions posed by themselves through a project that they develop in twelve sessions.